A novel p.E121G SOD1 mutation in slowly progressive form of amyotrophic lateral sclerosis induces cytoplasmic aggregates in cultured motor neurons and reduces cell viability. Issue 1 (March 2015) - Dangoumau, Audrey; Deschamps, Romain; Veyrat-Durebex, Charlotte; Pettmann, Brigitte; Corcia, Philippe; Andres, Christian R.; Vourc'h, Patrick
Abstract: Mutations in the SOD1 gene encoding the Cu/Zn superoxide dismutase-1 protein are responsible for amyotrophic lateral sclerosis (ALS), a fatal neurodegenerative disease. To date a large number of mutations have been reported in SOD1, but only few of them have been studied and validated by functional studies. We present a novel mutation in SOD1 in a female suffering from slowly progressive ALS. This dominant mutation (c.365A > G) in exon 5 resulted in a substitution of a highly conserved amino acid (p.E121G) of the protein. Functional studies in the motor neuronal cell line NSC34 and in primary culture of mouse motor neurons revealed that this mutation p.E121G induced aggregates positive for SOD1 and ubiquitin, as well as reduced cell viability. These findings identified a novel causal mutation in ALS in close proximity with one of the three histidine residues (H120) of SOD1 interacting with copper.